49.3: Highly Efficient OLED Devices with Device Architecture for Reducing Drive Voltage. Issue 1 (1st July 2013) - Kawata, Takuya; Seo, Satoshi; Shitagaki, Satoko; Inoue, Hideko; Seo, Hiromi; Hatsumi, Ryo; Tamatsukuri, Yuki; Yamaguchi, Tomoya; Kataishi, Riho; Sasaki, Toshiki; Suzuki, Tsunenori; Yokoyama, Kohei; et al.
Abstract We have developed phosphorescent OLEDs utilizing energy transfer from an exciplex to an emitter. The OLEDs based on this mechanism showed quite high efficiency, a long lifetime and low drive voltage. OLED lighting with high power efficiency exceeding 100 lm/W at a practical luminance of 5, 000 cd/m2 was also successfully developed.